Organization theory : (Penguin Books, 1984)
Spans seventy years of theory from Max Weber's seminal writings on bureaucratic organization to the management thinking represented by Handy, Peters and Waterman. This title covers three areas of interest, those of the structure of organizations, management and decision making, as well as that of organizational behaviour.